Repression of the synthesis of exocellular and intracellular proteinases in Bacillus megaterium - Moravcová, J; Chaloupka, J (Folia microbiologica, 1984)
The synthesis of exocellular proteinase decreases with increasing concentration of amino acids in the growth medium. After removal of amino acids the enzyme synthesis is gradually restored to normal values. The presence of inhibitors of transcription (actinomycin D) or translation (chloramphenicol) blocks the restoration of enzyme synthesis. No active or inactive precursors of the exocellular enzyme could be detected in the cell. It is likely that the enzyme synthesis is regulated by amino acids at the level of specific mRNA synthesis rather than at the translation level or at the level of secretion. The activity of the enzyme that has already been secreted to the external medium is partially inhibited by amino acids. The periplasmic proteinase is repressed by amino acids to the same extent as the exocellular enzyme. The content of the enzyme(s) inside the protoplast is also decreased during growth in the presence of amino acids.
Keywords: daktinomycin; kinetika; Enzyme Repression; Enzyme Activation; Peptide Hydrolases; Chloramphenicol; chloramfenikol; inhibitory proteas; Amino Acids; enzymová represe; proteasy; Protease Inhibitors; Dactinomycin; Bacillus megaterium; aminokyseliny; Kinetics; aktivace enzymů